Productivity Employee: Analysis of Employee Behavior, Competence, Task Performance, and Work Motivation - Susanto, Primadi Candra; Supardi Supardi; Agus Suhendra; Adi Soeprapto; Tubagus Hedi Saepudin (Dinasti International Journal of Digital Business Management, 2024)
This article is expected to provide added value for readers who are interested in human resource management, organizational leadership, or overall organizational development. This article uses qualitative by collecting article literature related to the variables in this article. Articles come from existing international journals such as Elsevier, Emerald, Springer, Willey and other international indices. Dozens of these articles will be described from the results of the research and taken from the perspective of the researcher. The results show that the integration of these findings in managerial strategies can help organizations achieve better operational efficiency and achieve their long-term business goals more consistently. By paying attention to and managing these factors well, the organization. By integrating these findings into a holistic and sustainable human resource management strategy, organizations can build a solid foundation for achieving long-term competitive advantage. In today's dynamic context of business, focusing on employee development as a key asset can be key to long-term success.